Preventative Cancer Treatments Through Optimizing Tissue Structure - Christopher Graser (Tinbergen Institute, 2020)
The likelihood of cancer emergence is highly dependent on the underlying tissue structure. This article gives evolutionary explanations for why natural selection fails to select for tissue structures that would minimize the likelihood of cancer. In a second step, a mathematical framework is proposed, within which the risk of cancer emergence can be expressed and calculated dependent on a given tissue structure. This can be used to identify optimal structures and strategies for improvement. Lastly, the article explores both, ways to identify target areas for such intervention, as well as avenues towards developing treatment options.
Keywords: Z00; C73; I10; 330; Evolution; Evolutionary Game Theory; Cancer